Alcohol and Relatively Pure Cannabis Use, but Not Schizotypy, are Associated with Cognitive Attenuations - Herzig, Daniela A.; Nutt, David J.; Mohr, Christine (Frontiers in Psychiatry, 2014)
Elevated schizotypy relates to similar cognitive attenuations as seen in psychosis and cannabis/polydrug use. Also, in schizotypal populations cannabis and polydrug (including licit drug) use are enhanced. These cognitive attenuations may therefore either be a behavioural marker of psychotic (-like) symptoms or the consequence of an enhanced drug use in schizotypal populations. To elucidate this, we investigated the link between cognitive attenuation and cannabis use in largely pure cannabis users (35 CU) and non-using controls (48 nCU), accounting for the potential additional influence of both schizotypy and licit drug use (alcohol, nicotine). Cognitive attenuations commonly seen in psychosis were associated with cannabis and alcohol use, but not schizotypy. Future studies should therefore consider i) non-excessive licit substance use (e.g. alcohol) in studies investigating the effect of cannabis use on cognition and ii) both enhanced illicit and licit substance use in studies investigating cognition in schizotypal populations.